2019
DOI: 10.3748/wjg.v25.i35.5356
|View full text |Cite
|
Sign up to set email alerts
|

De novo malignancies after liver transplantation: The effect of immunosuppressionn-personal data and review of literature

Abstract: BACKGROUNDImmunosuppression has undoubtedly raised the overall positive outcomes in the post-operative management of solid organ transplantation. However, long-term exposure to immunosuppression is associated with critical systemic morbidities. De novo malignancies following orthotopic liver transplants (OLTs) are a serious threat in pediatric and adult transplant individuals. Data from different experiences were reported and compared to assess the connection between immunosuppression and de novo malignancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 156 publications
(166 reference statements)
1
50
0
1
Order By: Relevance
“…Data from patients undergoing LT for HCC underscore the crucial role of immunosuppression type in patients’ outcomes by reducing the risk of HCC recurrence [ 145 ]. Moreover, in post-orthotopic LT, the incidence of de novo malignancies is 2–4 times higher than in the general population, with lymphoproliferative disorders and skin cancers being the most frequent ones [ 146 ].…”
Section: How We Treat Aild Patients With Hccmentioning
confidence: 99%
“…Data from patients undergoing LT for HCC underscore the crucial role of immunosuppression type in patients’ outcomes by reducing the risk of HCC recurrence [ 145 ]. Moreover, in post-orthotopic LT, the incidence of de novo malignancies is 2–4 times higher than in the general population, with lymphoproliferative disorders and skin cancers being the most frequent ones [ 146 ].…”
Section: How We Treat Aild Patients With Hccmentioning
confidence: 99%
“…Few studies have assessed the relationship between skin cancer risk and multidrug immunosuppression, although most OTR were treated with combinations of immunosuppressive drugs 19,22–26 . The present study found that treatment with three or more immunosuppressive drugs significantly increased the risk of developing new skin cancers.…”
Section: Discussionmentioning
confidence: 48%
“…It is presumed that long‐term immunosuppression increases the risk of recurrence of pretransplant malignancies and the risk of de novo malignancies . For example in this study, the risk of post‐transplant recurrence in patients with incidental colorectal cancers was 0% in stage 0 or I tumor, 33.3% in IIA tumor, and 100% in IIIA tumor, and 50% in stage IIIB tumor.…”
Section: Discussionmentioning
confidence: 57%